(untitled) (BIRDEM Medical Journal, 2023)
Class 4 emphysematous pyelonephritis with emphysematous cystitis is an uncommon diagnosis. We report a case of class 4 emphysematous pyelonephritis with emphysematous cystitis, occurring in a young Bangladeshi diabetic lady, who presented with features of upper urinary tract infection and the diagnosis of emphysematous pyelonephritis was confirmed by computed tomography scan. She was treated conservatively. BIRDEM Med J 2023; 13(3): 160-162